Dynamic structural reconstruction of (guanidinium+)2(benzene-1, 4-disulfonate2−) host crystal by guest adsorption. Issue 5 (6th January 2021) - Abe, Haruka; Kobayashi, Takahiro; Hoshino, Norihisa; Takeda, Takashi; Suzuki, Yasutaka; Kawamata, Jun; Akutagawa, Tomoyuki
Abstract : Guanidinium (G + ) and benzene-1, 4-disulfonate (BDS 2− ) form a rigid electrostatic cation–anion crystal lattice, which undergoes an interesting dynamic structural reconstruction through guest adsorption–desorption processes. Abstract : Guanidinium (G + ) and benzene-1, 4-disulfonate (BDS 2− ) form a rigid electrostatic cation–anion crystal lattice, which undergoes an interesting dynamic structural reconstruction through guest adsorption–desorption processes with H2 O, pyrrole (Pyrr), pyrazine (Pyz), thiophene (TP), pyridine (Py), 1, 4-dioxane (Diox), or aniline (Ani). The host lattice of bis(guanidinium)benzene-1, 4-disulfonate, (G + )2 (BDS 2− ), which does not contain void spaces initially, changed to host–guest crystals of (G + )2 (BDS 2− )·(guest) x upon guest adsorption ( x = 1, 2, and 3). The cation–anion electrostatic N–H + ⋯ − O3 S– hydrogen bonds between the G + cation and BDS 2− dianion formed tightly bound two-dimensional (2D) structures. These layers are connected by perpendicular BDS 2− dianions, forming the guest adsorption crystalline pores. The adsorption–desorption isotherm for Diox at 298 K indicated the formation of (G + )2 (BDS 2− )·(Diox)3, which was consistent with the single-crystal X-ray structural analysis. Single crystals of (G + )2 (BDS 2− )·(Py–H2 O)2 consist of two hydrogen-bonded [(G + )2 (BDS 2− )]2 bilayers connected by the BDS 2− dianions, forming crystalline pores that accommodate 2 Py guest molecules. The H2 O molecules in (G + )2 (BDS 2− )·(Py–H2 O)2 are lodged in the intralayer, leading to the [(G + )2 (BDS 2− )⋯(H2 O)2 ⋯(G + )2 (BDS 2− )] hydrogen-bonded bilayer. The electrostatic cation–anion host lattice of (G + )2 (BDS 2− ) responded to the guest adsorption–desorption cycle by a dynamic structural reconstruction. A guest adsorption of polar Ani into (G + )2 (BDS 2− ) host changed the crystal symmetry from centric P 1̄ to acentric P 21 of (G + )2 (BDS 2− )·(Ani)3 .